Mapping Commodities Production Level of Vegetables and Fruits in Kolaka District - Hariyanto, Eko; Tarmizi Abd Karim, Ahmad; Prasad Shrestha, Rajendra; Purbaningsih, Yuli; Ahwan Ikhsan, Fahrudi; Estining Sejati, Andri (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 16 No 2 (2022): Vol 16 No 2 (2022)DO - 10.24843/SOCA.2022.v16.i02.p01, 2022)
Farming development in the agricultural sector in Kolaka District has challenges in markets, supply, and production. This study aimed to analyze seasonal cropland phenomena' scaling and distribution principles, focusing on vegetable and fruit crops. This type of research is descriptive and quantitative. The research location is in Kolaka District, Southeast Sulawesi Province, Indonesia. The data collection technique used data from Kolaka District in Figures 2020 and the Kolaka Regional Medium-Term Development document. The data analysis technique uses a scaling method presented in the form of an interval table. Then the data is viewed from the point of view of the principle of economic geography distribution. The results of this study, firstly, the potential harvest area spread in each sub-district is chili with  ??158 hectares, then long beans, spinach, and kale. Second, seasonal fruit and vegetable production distribution in each sub-district is 2,048 quintals of chili, followed by eggplant, kale, long beans, and spinach. Meanwhile, data on scaling in harvested areas is very lacking, production potential is very less, and production levels are less. The recommendations for the potential development location of fruit and vegetable agriculture is Iwoimendaa Sub-district.